Improvements in the design of brine diffusers in shallow waters: A numerical study applied to the Canary Islands - Adrián Gil Trujillo; J. Jaime Sadhwani Alonso (Ain Shams Engineering Journal)
The desalination of seawater is a critical process for ensuring a dependable source of potable water, particularly in arid regions such as the Canary Islands. However, the disposal of brine presents considerable environmental and economic challenges. This study presents a comprehensive numerical analysis of brine diffuser design in shallow waters, with a particular focus on desalination plants in the Canary Islands. The Brine-Jet model is employed in order to evaluate the effects of key design variables, including nozzle height, discharge velocity and inclination angle, under a variety of velocity scenarios. This study presents a comprehensive analysis that, for the first time, identifies the critical importance of high nozzle height as a variable, particularly in low discharge rate scenarios. The findings of this study illustrate that even in shallow waters, elevated diffusers can confer significant benefits. Furthermore, a graphical design tool was developed to facilitate the clear visualisation of optimal diffuser configurations based on critical parameters such as dilution and plume height. The tool provides practical guidelines for improving diffuser designs, thereby ensuring more effective mitigation of the environmental impacts of brine discharge in coastal areas. Furthermore, the results emphasise the necessity for adaptable infrastructure to accommodate seasonal variations in water demand and increasingly stringent environmental regulations. This research offers a solution for optimising brine disposal, thus contributing to the development of sustainable and efficient desalination outfalls in similar marine environments.